Analysis of externally bonded Carbon Fibre Reinforced Polymers sheet to timber interface. (1st May 2018) - Vahedian, Abbas; Shrestha, Rijun; Crews, Keith
Abstract: The performance of FRP composite bonded externally to timber is complex and to date, limited attempts have been made to investigate the bond behaviour of FRP to timber interface. Furthermore, analytical solutions to determine the interface behaviour of FRP to timber have not been fully investigated and are not covered in current Standards. The objective of the present study is to develop a functional and efficient analytical model to accurately predict the behaviour of FRP-to-timber joints. This research study has been performed using 136 FRP-to-timber joints subjected to pull-out tests, and accordingly a new predictive model for determination of the strain distribution profile, slip profile and shear stress along the interface has been established. A comparative analysis of the results of the experimental pull-out tests results and those predicted from the analytical model indicates a satisfactory correlation is achieved between measured and predicted parameters. The assessment results show that the proposed strain model is rather conservative at 80% of the ultimate load, while slightly underestimates strain distribution profile at ultimate load. High correlation was obtained for the proposed shear stress and bond-slip models against the experimental at ultimate load. Finally, significant improvement in prediction has been achieved when results of the proposed analytical models compared with the existing models from the literature, signifying the capability of the new models.